EFFECTS OF PATIENT COUNSELING ON DRUG DOSE REGIME AND MEDICATION COMPLIANCE IN ASTHMA PATIENTS: A PROSPECTIVE STUDY - OMAR, SHIPRA; BANGWAL, ROHIT; SHARMA, SAHIL; MATHUR, PRASHANT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objective of study is to estimate the role of counseling on the diseased patients with asthma and its effects on the medication adherence in relation to their associated side effects on medicines on patients. Methods: The prospective case–control study was carried out at the outpatient department of respiratory department. 190 patients were enrolled for the study of 6 months. Patient counseling and follow-up were done on the basis of knowledge, attitude, and practice (KAP) questionnaire. In 190 subjects, 115 were female and 75 were male and were having the pathological history of cough cold, tuberculosis, hypertension, etc. Results: It was found that counseling causes increase in medication adherence of patients from 28.90% to 71.50% and inhaler adherence from 27.60% to 72.60%. Along with the medication adherence, fewer side effects due to various drugs were encountered such as sore throat, rhinitis, constipation, difficulty in glutition, hand tremor, and weight gain. Conclusion: The study concluded that, patient counseling plays an important role in diseases like asthma, which changes the attitude, increases the knowledge which turns out into the better medication results improving the asthmatic symptoms.